Are the Leadership Style and Motivation Influence the Work Performance of Health Center Personnel? - Indriastuti, Latty; Sulaeman, Endang Sutisna; Pamungkasari, Eti Poncorini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: The performance of an organization is largely determined by the human resources in it. If the human resources are highly motivated, creative and innovative and are led by leaders who are responsible and have good leadership skills, their performance will be good. This study aims to analyze the influence of the leadership style of the head of the puskesmas and the work motivation of the employees on the performance of the employees of the Puskesmas Ciamis District.Subjects and Method: This study was conducted using a cross sectional research design. The study was conducted in Ciamis Regency in November – December 2020. Sampling was carried out using random sampling with a total of 200 puskesmas employees in Ciamis Regency. The dependent variable is employee performance. The independent variables include leadership style, work motivation, job satisfaction, education, treatment status, employee status, length of work. Data were collected by questionnaire and analyzed using a multilevel multiple logistic regression.Results: Good leadership style (b=3.58; 95% CI= 1.11 to 3.80; p= 0.000), high work motivation (b=3.12; 95% CI= 0.83 to 3.65; p= 0.002), have job satisfaction (b= 2.89; 95% CI= 0.67 to 3.53; p= 0.004), higher education (b= 2.89; 95% CI= 0.60 to 3.13; p= 0.004), inpatient care status (b= 2.66; 95% CI= 0.47 to 3.12; p= 0.008), health personnel status (b=3.68; 95% CI= 1.46 to 4.80; p= 0.000), and length of service 3 years (b=2.07; 95% CI= 0.78 to 2.76; p= 0.038) increase the possibility of the performance of puskesmas employees. Variations at the puskesmas level show that there is a contextual effect on employee performance (ICC= 11.75%). Conclusion: There is a positive and statistically significant effect on leadership style, work motivation, job satisfaction, education, treatment status, employee status, length of work on the performance of puskesmas employees. Variations at the puskesmas level show that there is a contextual effect on employee performance.Keywords: employee performance, leadership style, health center, Correspondence: Latty Indriastuti.Masters Program in Public Health, Universitas Sebelas Maret, Surakarta, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: lattyindria.drg@gmail.com. Mobile: +628999976544.Journal of Health Policy and Management (2021), 06(03): 168-181https://doi.org/10.26911/thejhpm.2021.06.03.02